Availability and Accessibility of Orphan Medicinal Products to Patients in Slovakia in the Years 2010–2019 - Foltanova, Tatiana; Majernik, Alan; Malikova, Eva; Kosirova, Stanislava (Frontiers in Pharmacology, 2022)
Objective: Information about the access of Slovak patients to orphan medicinal products (OMPs) in the literature is rather scarce. The main aim of the paper was to analyze the accessibility and availability of OMPs to Slovak patients in the years 2010 – 2019. Methods: The analyzed OMPs were strictly defined according to European definition. Date of marketing authorization together with first appearance in the positive drug list were used to count the time to reach the national market. The data from the National Health Information Centre, Ministry of Health and health insurance companies were used as data sources of drug usage, expenditure, consumption and reimbursement of OMPs as well as the total number of treated patients. Results: Out of the 167 OMPs on the European market, we identified 52% (87) OMPs which had any kind of costs recorded in Slovakia. Out of them 62% (54) OMPs were directly present in the positive drug list. The remaining 33 OMPs were available on exception. The trend in accessibility and availability of OMPs in Slovakia between the years 2010 – 2019 was decreasing (57% OMPs in 2010 vs 47% OMPs in 2019). The average time for an OMP to reach the Slovak market was almost 4 years, 43.5 months [6 – 202 months]. Together 10.4% (8 815 patients) out of the theoretical patients' estimation according to the prevalence in the orphan designation were treated with OMPs available in Slovakia. Conclusion: Presented data clearly shows insufficient accessibility and availability of OMPs in Slovakia. Importance of clearly defined criteria for OMPs supporting patients and healthcare professionals’ involvement in the final decision together with other measures such as social impact, improvement of patients’ quality of life, society wide meaning or no alternative treatment in the final decision are crucial for transparent and sustainable access to OMPs and innovative treatments in Slovakia.